Migration and institutions: the case of the Veneti. Issue 5 (20th October 2018) - Strangio, Donatella
ABSTRACT: In order to maintain some forms of belonging and a distinct ethnic identity during the migration process, combining elements from the original country with others already active in the country of settlement can prove effective in responding to the various needs of the people involved. Institutions play an important role in attracting or assimilating migratory flows within host countries and in engaging migrants, through a particular institution such as 'ethnic specialization' in the labour market (e.g. the case of the Veneti in the agricultural field) and (less frequently) residential segregation in urban areas. This theoretical aspect becomes concrete in the empirical relationship between institutions and migration; it will highlight the role of the institutions in this area through an underlying common denominator which consists in a selected Italian regional population, the Veneti . The analysis will involve two different contexts, Italy and Brazil, in which the Veneti worked within the same historical time frame. This article will try to contribute to the debate by both reducing the heterogeneity of the addressed topic and applying a historical perspective. The case study is the population of an Italian region: Veneto in the North of Italy. The article will be structured as follows: (1) Theoretical background: migration, economic development and the role of institutions; (2) The Veneti in Brazil; (3) The Veneti in Pianura Pontina; and (4) Discussion and Conclusion